Atividade de ectoenzimas do sistema purinérgico e análise de biomarcadores inflamatórios e de estresse oxidativo em pacientes com câncer de pulmão - Zanini, Daniela (2014)
Lung cancer has been considered a public health problem since it has become one of the most commonly diagnosed neoplastic diseases and one of the most lethal in the world. This spread of lung cancer in the world population has been clearly observed in statistics and has been closely related to tobacco consumption. Cigarette smoking is considered one of the major risk factors that has led to cancer development since the 50s. Researches have shown that there is a close relationship between smoking inflammation - prothrombotic events - lung cancer. In this context, the analysis of biomarkers of inflammation is important since inflamed sites are conducive to tumor development environments. Furthermore, it is important to study the activity of ecto-nucleotide triphosphate diphosphohydrolase (E-NTPDase), ecto-5'-nucleotidase and ecto adenosine deaminase (E-ADA) enzymes which are engaged in regulating the levels of adenine nucleotides and nucleoside widely involved in inflammation and platelet aggregation. Oxidative stress is associated with the development and progression of cancer. Thus, it is extremely important to evaluate the aspects of cellular functions in a group of patients with lung cancer. The objectives of this study were i) to verify the serum levels of cytokines such as IL-6, IL-17, IL-4, IL-2, IL-10, interferon- (IFN-) and Tumor Necrosis Factor (TNF); ii) to evaluate the activity of the E-NTPDase, E-NPP, ecto-5'-nucleotidase and E-ADA platelets, and platelet aggregation; iii) to evaluate the activity of δ-aminolevulinic acid dehydratase (δ-ALA-D) erythrocyte, the levels of thiobarbituric acid reactive species (TBARS) in platelet and of reactive species (RS) in serum species; and iv) to analyze the enzymatic antioxidant profile - through the activity of superoxide dismutase (SOD) and catalase (CAT) in platelets - and non-enzymatic profile - through the content of total thiols (T-SH) and non-protein thiols (NPSH) in platelet and of the levels of vitamin C in plasma vitamin E in serum. The study group had non-small cell lung cancer and was treated at the Hematology/Oncology Section at the University Hospital of Santa Maria. The project was approved by the Ethics Committee of the Federal University of Santa Maria, CAAE (Certificate of Appreciation Presentation for Ethics) and is registered under number: 0061.0.243.000-10. Results showed that patients with lung cancer presented an increase in serum levels of IL-6, which are closely related to the development and progression of tumor, since this cytokine has proinflammatory and pro-tumor activities. The levels of IL-17 were decreased in these patients, which may be related to the advanced stage of the development of lung cancer in these subjects. Patients with lung cancer showed a decrease in E-NTPDase activity for the hydrolysis of ADP, which contributes to the expansion of procoagulant effects commonly observed in patients with neoplastic diseases.This hypothesis is strengthened by the increased platelet aggregation observed when ADP was used as the agonist process. Patients enrolled in this study showed a decrease in the CD39 expression in platelets, which is in agreement with that observed for the NTPDase activity in platelets.The studied group had an increase in the ecto-5'-nucleotidase activity and a decrease in the E-ADA activity in platelets. This suggests that the extracellular adenosine levels were elevated leading to the advance of the tumor development due to the promoting actions characteristics of adenosine such as tumor growth and of stimulating angiogenesis. Regarding the oxidative profile, the activity of δ-ALA-D enzyme was inhibited in patients with lung cancer, which may predict the occurrence of oxidative stress in these patients. This scenario can be confirmed by the elevated levels of TBARS and RS observed in patients with lung cancer. This overproduction of oxidants may also be causing the inhibition of SOD and CAT enzymes in platelets and thus their structure and the function may be compromised. Furthermore, there was a decrease in the levels of important non-enzymatic antioxidants in patients with lung cancer, showing that their beneficial actions may be occurring in an insufficient way. High levels of T-SH and possibly glutathione are implicated in the development of tumor resistance to chemotherapy. Therefore, the results described here suggest that lung cancer exerts a significant change in serum levels of IL-6 and IL-17, in the activity of the enzymes of the purinergic system in platelets, as well as in the oxidative profile of these patients. Thus, it is hoped that this work may have contributed to a better understanding of the role of the purinergic system and biomarkers of inflammation and oxidative stress in the pathophysiology of lung cancer.